Protocells programmed through artificial reaction networks. Issue 3 (7th January 2020) - Lyu, Yifan; Peng, Ruizi; Liu, Hui; Kuai, Hailan; Mo, Liuting; Han, Da; Li, Juan; Tan, Weihong
Abstract : In this review, the milestones and recent progress of protocells programmed by various types of artificial reaction networks are highlighted. Abstract : As the smallest unit of life, cells attract interest due to their structural complexity and functional reliability. Protocells assembled by inanimate components are created as an artificial entity to mimic the structure and some essential properties of a natural cell, and artificial reaction networks are used to program the functions of protocells. Although the bottom-up construction of a protocell that can be considered truly 'alive' is still an ambitious goal, these man-made constructs with a certain degree of 'liveness' can offer effective tools to understand fundamental processes of cellular life, and have paved the new way for bionic applications. In this review, we highlight both the milestones and recent progress of protocells programmed by artificial reaction networks, including genetic circuits, enzyme-assisted non-genetic circuits, prebiotic mimicking reaction networks, and DNA dynamic circuits. Challenges and opportunities have also been discussed.